The Art of Scaling Deep - Research in Summary - and Fraser, Tatiana (The Systems Sanctuary)
Over the last 15 years the concept of scale has become a foundational part of the apparatus of the social and environmental change sector. A business mindset of growth has been seamlessly transferred to the social and environmental problems we are collectively trying to shift in the world. Scaling up, (influencing policy) has been considered the strategic pathway to systems change. Scaling out (spreading new models) is seen as a pathway to success. The allure of these scaling theories lies, in part, in their tangibility, and the easy way in which they can be measured. However this focus on growth has shifted our attention away from a series of messy truths. Sometimes bigger isn't better. Endless growth is not sustainable and our urgency to try to fix the problem and seek solutions may be part of the crisis we are in. One unintended consequence of this has been that another type of scale has been devalued and as a result, under-resourced. It’s a scale that values the slow steady work of deepening relationships. It recognizes the significance of context, building connections that bridge diverse communities and it prioritizes inner work and healing as integral components of the scaling process. We call this type of scale ‘Scaling Deep’ and we believe that adequately supporting it, and funding it, holds the greatest potential for long lasting systemic change. The purpose of this research has been to delve deeper into the art and craft of Scaling Deep. Ultimately, our goal is for it to become firmly ingrained within the recognized realm of social change, alongside the well-established concepts of scaling up and scaling out. We want practitioners who are Scaling Deep to be able to harness the wisdom and power of this work and to talk about it openly, with confidence and credibility. We want understanding of this approach to flourish and evolve and for it to be appropriately celebrated and supported. We want decision-makers to be informed and inspired by the principles and practices of scaling deep. For it to be embedded in theories of change as an essential component of decision-making processes within the wider change discourse. Importantly we want leaders who are Scaling Deep to have access to sufficient resources and to receive the care from the field that they need to thrive. We would like to see organisations that have the power to invest, to align their efforts with the profound impact that scaling deep aspires to cultivate in the world. Before we begin, let us be crystal clear. We are not opposed to scaling up and out as strategies for change. Innovation and scaling what is working is part of how we evolve as humanity. As social entrepreneurs ourselves, we have both done this twice over. We value it and we know it’s important. We recognize these are strategies for creating widespread impact and effecting positive change. Our intention here is not to dismiss or undermine the value of scaling up and out, but rather to encourage a broader and more holistic perspective that includes other dimensions of scale. There is a need to understand how the different scaling approaches can work together, rather than seeing them as hierarchical and disconnected. Our ultimate goal is to equip the change sector with a more inclusive, expansive, and powerful approach to tackling the myriad challenges we face, by exploring the potential of Scaling Deep as a transformational strategy for systems change.